Answer:
Step-by-step explanation:
(3x+1)(x-3)-(2-2x^2-3x)
3x^2+x-9x-3-2+2x^2+3x
3x^2+2x^2+x-9x+3x-3-2
5x^2-5x-5
the constant term in the simplified expression is -5.
<span>6x-7y=-84
7y = 6x + 84
y = 6/7(x) + 12</span>
Answer:
(y - 6) = 3/5(x - 5)
Step-by-step explanation:
First, let's look at what point-slope form is: (y - y₁) = m(x - x₁)
Let's plug in the vallues we know.
m is the slope: 3/5
x₁ is 5
y₁ is 6
Therefore:
(y - 6) = 3/5(x - 5)
This is your equation.
Hope this helps!
Answer:
B
Step-by-step explanation:
These lines dont cross CD and are not parrellel which is what skew lines are.
Answer:
independent
Step-by-step explanation:
because each chocolate was a different flavor